2019
DOI: 10.1002/adem.201901229
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Powder Metallurgy‐Fabricated Oxygen‐Containing Beta Ti–Nb–Mo–Sn–Fe Alloys for Biomedical Applications

Abstract: The influence of minor oxygen additions on the microstructure and mechanical properties of powder metallurgy (PM) fabricated Ti–25Nb–5Mo–3Sn–2Fe alloy is studied. The results demonstrate the positive influence of a certain oxygen content (0.35 wt%) on the microstructure and mechanical properties of sintered samples. Despite the presence of 7.0% porosity in the PM‐fabricated samples of Ti–25Nb–5Mo–3Sn–2Fe–0.35O, a high strength of 682 MPa, elongation of 7.2%, and Young's modulus of 74 GPa are obtained. The stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…We double-checked these records and concluded that the oxygen contents in Xu et al . 27 were indeed reported right; these specific studies are simply unusual, with relatively high oxygen additions 28 . Entries with extreme elongation were associated with specimens that did not fracture during mechanical testing; deformation at rupture values from these studies 25 , 29 32 were set to a maximum of ±50%.…”
Section: Technical Validationmentioning
confidence: 79%
“…We double-checked these records and concluded that the oxygen contents in Xu et al . 27 were indeed reported right; these specific studies are simply unusual, with relatively high oxygen additions 28 . Entries with extreme elongation were associated with specimens that did not fracture during mechanical testing; deformation at rupture values from these studies 25 , 29 32 were set to a maximum of ±50%.…”
Section: Technical Validationmentioning
confidence: 79%
“…Metal powders can be pre-alloyed [44,45] or mechanically alloyed [34,46]; it depends on the application sought. PM seeks added value for use on an industrial scale, such as biomedical implants using wear-resistant titanium alloys [47][48][49] or in the manufacture of hard metals for cutting tools or coatings [50]. Currently, one of its main applications is in the automotive industry for the manufacturing of small and complex components.…”
Section: Introductionmentioning
confidence: 99%